Bacterial Endophytes from Vitis vinifera L. – Metabolomics Characterization of Plant‐Endophyte Crosstalk. Issue 12 (27th October 2021) - Stranska, Milena; Lovecka, Petra; Vrchotova, Blanka; Uttl, Leos; Bechynska, Kamila; Behner, Adam; Hajslova, Jana
Abstract: Bacterial endophytes are known to protect Vitis vinifera L. against various harmful effects of the environment and support its growth. However, for the most part, biochemical responses of such co‐existence have not yet been fully elucidated. In this work, we aimed to characterize the activities of endophytic consortia in a plant‐endophyte extract by measuring five indicators of colonization (overall endophyte metabolic activity, microbial ACC deaminase activity, ability to solubilize phosphorus, ability to convert atmospheric nitrogen to ammonia ions, and ability to produce growth promoting indole acetic acid), and find relationships between these activities and metabolome. The V. vinifera canes for the metabolomics fingerprinting were extracted successively with water and methanol, and analysed by ultra‐high performance liquid chromatography coupled with high resolution mass spectrometry. For data processing, the MS‐DIAL – MS‐CleanR – MS‐FINDER software platform was used, and the data matrix was processed by PCA and PLS‐DA multivariate statistical methods. The metabolites that were upregulated with the heavy endophyte colonization were mainly chlorins, phenolics, flavonoid and terpenoid glycosides, tannins, dihydropyranones, sesquiterpene lactones, and long‐chain unsaturated fatty acids. Abstract :